Prove that tan 70circ = tan 20circ + 2 tan 50circ

tan 70 = tan (20 + 50) 

tan (A + B) = (tan A + tan B) / [1 – tan A tan B]

tan 70 = (tan 20 + tan 50) / [1 – tan 20 tan 50] 

tan 70 tan 20 = tan 70 cot 70 = 1 …….. [tan (90 – B) = cot B] 

tan 70 – tan 50 = tan 20 + tan 50 

tan 70 = tan 20 + 2 tan 50

Was this answer helpful?

 
   

0 (0)

(0)
(0)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

BOOK

Free Class

Ask
Question